FINANCIAL RATIO ANALYSIS IN PREDICTING FINANCIAL DISTRESS OF FOOD AND BEVERAGE COMPANIES WITH LOGISTIC REGRESSION - Azis, Yunia Mulyani (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2021)
The purpose of this study is to analyze the effect of financial ratios such as leverage, liquidity, activity, and profitability on the possibility of financial distress (financial distress). The population in this study are all food and beverage companies listed on the Indonesia Stock Exchange in the period 2017 - 2020 totaling 30 companies. The samples taken were 6 food and beverage companies using a purposive sampling technique, namely the selection of samples based on certain criteria. The number of observations that were processed and analyzed were 18 observations. Logistics Regression is the method used in this research. The results showed that the activity ratio and leverage ratio had a significant effect on predicting financial distress, while the liquidity ratio and profitability ratio had no significant effect on predicting financial distress..